An examination of teaching strategies for mediating the construction of environmental content knowledge: a case of Grade 11 Life Sciences teaching in two Eastern Cape schools - Chitsiga, Christina (Rhodes University, Faculty of Education, Department of Education, 2016)
In South Africa the new Curriculum Assessment and Policy Statement (CAPS) introduced a more strongly content referenced curriculum which has commitments to active and critical approaches to learning, and to environment and sustainability content. Successful implementation of CAPS requires that teachers attain the requisite knowledge and pedagogical content knowledge for working with environmental and sustainability content. The study examined teachers' knowledge of environmental content as well as how teachers are mediating learning, through exploring the classroom techniques used by teachers working with environmental content. This was to examine how teachers are through their teaching bridging the gap in the understanding, investigation and application of environmental content in the curriculum. The study used a number of approaches from the field of environmental education which offer different lenses (or pedagogical sensitizing constructs) for viewing mediation processes as a relational process of knowledge construction. These pedagogical constructs were: knowledge co-construction where perspectives and understandings are shared in the process of social relations (deliberation); relating environmental content knowledge to cultural historical context (situated learning); relating environmental content knowledge to everyday and intergenerational knowledge through hands on experience (proximity experience) and developing an iterative relationship between environmental content knowledge and sustainability practices (practical reasoning). Practice theory as suggested by Schatzki (2005) and a theory of practice architectures elaborating on Schatzki's practice theory (Kemmis & Heikkinen, 2011) was used as the ontological lens to help in understanding the mediation of environmental content knowledge. Practice theory was used for exploring pedagogical practice in terms of sayings, doings and relatings by teachers, and practice architectures that represent enabling or constraining factors of teachers practice. This research was an interpretive case study drawing on findings from lesson observations, semi structured interviews, stimulated recall interviews and document analysis. The research found that teachers used different strategies to enhance their environmental content and pedagogical content knowledge to present the mediation. Teachers are supporting situated learning and deliberation in environmental learning. Another finding was that teachers could be enabled to enhance proximity experiences and practical reason in their mediating approaches in environmental learning. The research further showed that teachers could benefit from teacher professional development programmes that explicitly develop pedagogical content knowledge to support critical deliberation, proximity encounters, situated learning and practical reasoning in order to work with the diverse complex places-based, socio-cultural-historical nature of environmental curriculum content in the context of sustainability practices. Findings also showed that there were constraining factors to mediation of environmental learning. These constraining factors from the research were firstly in material economic arrangements of timetable compliance in CAPS, ability to find internet resources and availability of resources. Secondly, present were constraining factors of socio-political arrangements of CAPS curriculum document prescriptiveness, multiculturalism, learning institution management and governance. Thirdly, cultural discursive arrangements of teacher learner language, knowledge of the language of the field affected mediation. Teachers passion for environmental content topics, the ability of teachers' to improvise resources in mediating environmental content lessons and the ability of teachers' to navigate a stringent CAPS timetable were found in this research to be enabling mediation. Recommendations from the research are ongoing teacher refresher workshops on the environmental content in the CAPS curriculum, teachers' need more input on strategies to mediate environmental content, teachers' prior knowledge of new knowledge can be used to strengthen teacher professional development processes, teachers' prior knowledge needs to be deepened and reinforced, there is need to develop quality educational resources encompassing a variety of pedagogical sensitizing constructs and support needs to be given for familiarising teachers with teaching materials and their appropriate use . These could help to strengthen mediation of environmental content knowledge in the Grade 11 CAPS Life Sciences and inform South African teacher professional development programmes seeking to understand classroom practices in relation to environmental content.
Keywords: Uncatalogued